1998
DOI: 10.1115/1.2841412
|View full text |Cite
|
Sign up to set email alerts
|

Computational Prediction of Heat Transfer to Gas Turbine Nozzle Guide Vanes With Roughened Surfaces

Abstract: The local Mach number and heat transfer coefficient over the aerofoil surfaces and endwalls of a transonic gas turbine nozzle guide vane have been calculated. The computations were performed by solving the time-averaged Navier–Stokes equations using a fully three-dimensional computational code (CFDS), which is well established at Rolls-Royce. A model to predict the effects of roughness has been incorporated into CFDS and heat transfer levels have been calculated for both hydraulically smooth and transitionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The experimental data used to validate the computational fluid dynamic (CFD) results are taken from Newton [27]. The uncertainty in the temperature measurement was approximately 1%, which resulted in 5% uncertainty in the experimental value of heat-transfer coefficient and film-cooling effectiveness [28,29]. Figure 5 shows the predicted and measured static-pressure distribution on the end wall.…”
Section: Computational Fluid Dynamic Validationsmentioning
confidence: 99%
“…The experimental data used to validate the computational fluid dynamic (CFD) results are taken from Newton [27]. The uncertainty in the temperature measurement was approximately 1%, which resulted in 5% uncertainty in the experimental value of heat-transfer coefficient and film-cooling effectiveness [28,29]. Figure 5 shows the predicted and measured static-pressure distribution on the end wall.…”
Section: Computational Fluid Dynamic Validationsmentioning
confidence: 99%
“…On the other hand, manufacturers use directly measurable quantities Ra, Rq and Rz to represent the surface texture of their products. Equations available in literature [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] that try to relate these parameters vary greatly and there is no consensus on a single relation on these parameters. Equations proposed by [19][20][21][22][23][24] mostly use sand grains, emery papers or machined surfaces to produce the empirical equations using Ra, while suggested equations for groove height or liquid crystal surfaces, Rq [26][27] is mostly used for surfaces with sprayed particles as an alternative.…”
Section: Figure 5 -Measurement Of Surface Profilementioning
confidence: 99%
“…Naturally occurring calcination deposits were not studied in any of these works; however, for a wide range of surfaces, a general trend is to use Rz, peak to valley roughness height, equal to surface roughness value (ε) (Rz ≈ ε) [16] [17]. This corresponds to 287.45 μm for the calcinated surface sample.…”
Section: Figure 5 -Measurement Of Surface Profilementioning
confidence: 99%
“…Blair used Han's method (1985)for calculating the local friction coefficients as a common input to the four rough surface heat transfer correlations. Guo et al (1996) measured vane heat transfer in an annular rig using liquid crystals with a reported roughness R. of 25 micrometers, and also a smooth surface R. of less than 1 micrometer with thin film heat flux gages. R z is defined as the average peak-to-peak roughness height measured with a profilometer.…”
Section: Introductionmentioning
confidence: 99%
“…Blair (1992) and Boyle (1993) suggested that k s = R 2 . Dunn et al (1992) used Ic s = R / (13 and Guo et al (1996) found that k s = Rz for the best comparison of their experimental data. Bogard et al (1996) adopted a roughness shape / density parameter of Sigal and Danberg (1990) to characterize vane roughness, and then modeled large scale, flat plate surfaces to mimic this parameter value.…”
Section: Introductionmentioning
confidence: 99%